Volumetric modulated arc therapy based total marrow and lymphoid irradiation: Workflow and clinical experience - Ladbury, Colton; Han, Chunhui; Liu, An; Wong, Jeffrey Y. C. (Frontiers in Oncology, 2023)
Background: The aim of this study is to report historical treatment planning experience at our institution for patients receiving total marrow and lymphatic irradiation (TMLI) using volumetric modulated arc therapy (VMAT) as part of the conditioning regimen prior to hematopoietic stem cell transplant. Methods: We identified a total of fifteen patients with VMAT TMLI, ten with a prescription dose of 20 Gy (targeting the skeletal bones, lymph nodes, spleen, and spinal canal, with 12 Gy to the brain and liver) and five with a prescription dose of 12-16 Gy (targeting the skeletal bones, lymph nodes, spleen, and spinal canal). Representative dosimetric parameters including total treatment time, mean and median dose, D80, and D10 (dose covering 80% and 10% of the structure volume, respectively) for targets and normal organs were extracted and compared to historical patients treated with helical tomotherapy. Results: The median treatment time for the first and subsequent fractions was 1.5 and 1.1 hours, respectively. All the target volumes had a mean dose greater than the prescribed dose except the ribs, which had an average mean dose of 19.5 Gy. The skeletal bones had an average mean dose of 21.1 Gy. The brain and liver have average mean doses of 14.8 and 14.1 Gy, respectively. The mean lung dose had an average of 7.6 ± 0.6 Gy for the 20-Gy cohort. Relative to the prescription dose of 20 Gy, the average mean dose for the normal organ volumes ranged from 16.5% to 72.0%, and the average median dose for the normal organs ranged from 16.5% to 71.0%. Dosimetry for patients treated to 12-16 Gy fell within expected ranges based on historical helical tomotherapy plans. Conclusions: Dosimetric data in the VMAT TMLI plans at our institution are summarized for 20 Gy and 12-16 Gy cohorts. Dose distributions and treatment times are overall similar to plans generated with helical tomotherapy. TMLI may be delivered effectively using a VMAT technique, even at escalated doses.